APLIKASI PELAKSANAAN STANDAR OPERASIONAL PROSEDUR PENGOLAHAN LIMBAH PADAT LABORATORIUM DI RSUP DR. M. DJAMIL PADANG - Rinda Lestari (JURNAL KESEHATAN PERINTIS, 2017)
Hospital waste comes from health service units in hospitals including laboratories. All types of waste in the laboratory can be declared as infectious material, therefore the handling and disposal of waste must be handled properly so as not to cause negative impacts as a result of laboratory operations which if not managed properly can pollute the environment. Basically, waste management in hospitals must be done well and correctly according to the existing Standard Operating Procedure (SOP). So the writer is interested in examining the Application of the Implementation of Standard Operating Procedure (SOP) on Solid Waste Treatment in Dr. RSUP. M. Djamil Padang. The purpose of this study was to determine the compliance of officers in implementing SOPs for processing solid laboratory waste at Dr. RSUP. M. Djamil Padang. This type of research is a descriptive observational study with a cross sectional study approach, which is managing data from observations in the field by comparing the Standard Operating Procedures (SOP) that exist qualitatively. Primary data obtained from observations and checklists using prepared questionnaires. From the results of research conducted, it was found that 83% of SOPs had been carried out by laboratory cleaners and 17% of SOPs had not been carried out by laboratory cleaners. This is due to the unavailability of facilities needed by officers.